2011
DOI: 10.1021/ci200313r
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT1A Agonism Potential of Substituted Piperazine-Ethyl-Amide Derivatives Is Conserved in the Hexyl Homologues: Molecular Modeling and Pharmacological Evaluation

Abstract: In a series of carboxamide and sulphonamide alkyl (ethyl to hexyl) piperazine analogues, although the size of the linker is very different, ethyl and hexyl derivatives possess a high affinity for 5-HT(1A) receptors. Docking studies clearly show that hexyl and ethyl compounds favorably interact with the binding site of the active conformation of 5-HT(1A) receptors, thus confirming a possible agonist profile. This activity is effectively detected in electrophysiological experiments in which all four compounds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Docking experiments showed that the two most potent compounds of this series at the 5-HT 1A receptor (11b and 11d) exhibited a binding mode in which the main contact was the well-described coulombic interaction between a protonated nitrogen atom of the piperazine ring and Asp116 [8,9,20,21]. Interestingly, in the case of compounds 11a and 11c, this interaction was absent, which agrees with the lower affinity exhibited by these derivatives (Fig.…”
Section: -Benzylsupporting
confidence: 71%
“…Docking experiments showed that the two most potent compounds of this series at the 5-HT 1A receptor (11b and 11d) exhibited a binding mode in which the main contact was the well-described coulombic interaction between a protonated nitrogen atom of the piperazine ring and Asp116 [8,9,20,21]. Interestingly, in the case of compounds 11a and 11c, this interaction was absent, which agrees with the lower affinity exhibited by these derivatives (Fig.…”
Section: -Benzylsupporting
confidence: 71%
“…[45,47,150,151] Homology models were used for docking into neuronal nicotinic receptor, [152] Trypanosoma brucei phosphodiesterases, [153] prostaglandin E synthase 1, [154] aryl hydrocarbon receptor transcription factor, [155] as well as VS against the following: the s1 receptor, [156] calpain, [157] kinases, [158][159][160][161] and GPCRs. [45,47,126,151,[162][163][164][165] Structural validation studies For us to have an expectation that a given docking setup (i.e., choice of program, scoring function, and approaches to deal with ligand and receptor flexibility) will deliver reliable results, it must be validated for a system under investigation (i.e., ligand and receptor type). It is critical that users assess their unique docking setup(s) prior to embarking on a docking project: either by searching the literature (to check whether such validation has already been performed) or by performing it, if necessary.…”
Section: Docking Into Homology Modelsmentioning
confidence: 99%
“…The GPCR modeling and docking studies dealt with a variety of issues: validation of Prime homology models by VS with Glide (nine publicly accessible models: dopamine (D 2 , D 3 , and D 4 ), serotonin (5-HT 1B , 5-HT 2A , 5-HT 2B , and 5-HT 2C ), histamine (H 1 ), and muscarinic (M 1 ) receptors); [47] use of ensemble of alternative receptor conformations to account for its flexibility; [46] fragment screening by PLANTS (histamine H 1 receptor); [126] receptor subtype selectivity with DarwinDock (H 3 versus H 1 , H 2 , and H 4 receptors) [163] and ICM (adenosine receptors A 1 , A 2A , A 2B , and A 3 ). [48] agonist profiling (serotonin 5-HT 1A receptor); [164] design of novel ligands for adenosine A 2A [171,172] and dopamine D 3 . [173] receptors; development of universal active probes; [162] a comparison of Glide, Gold, and ICM-Pro for docking into the homology model of the 5-HT 2A receptor; [165] and peptide docking with photoaffinity labeling constraints in ICM-Pro.…”
Section: Kinasesmentioning
confidence: 99%
“…Crystal structure was subjected to protein preparation wizard for filling missing loops and side chains (using Prime), ionization, H-bond optimization, heterogeneous state generation, protonation and overall minimization. All other ligands, water and ions were removed except ATP molecule [46][47][48][49]. Grid file for docking was constructed considering ATP molecule as centroid of grid box of 10 ֩ A size [50][51].…”
Section: Protein Preparation and Dockingmentioning
confidence: 99%